PENGARUH PENDIDIKAN KESEHATAN DENGAN MEDIA VIDEO TERHADAP PENGETAHUAN TENTANG MANFAAT KONSUMSI TABLET TAMBAH DARAH SAAT MENSTRUASI PADA REMAJA PUTRI DI PONDOK PESANTREN JAMIYYATUL QURRO’ - Emy Kurniawati; Asti Hardiyanti; Hana Rosiana Ulfah; Ilma Widiya Sari; Bambang Sudono Dwi Saputro (STIKES Estu Utomo, 2025)
Background: Knowledge of young women about the benefits of consuming blood supplement tablets during menstruation will influence their behavior in consuming blood supplement tablets during menstruation and reduce problems that arise. Young women who have good knowledge about the benefits of consuming blood supplement tablets during menstruation tend to consume blood supplement tablets more often during menstruation. Objective: This study aims to determine the effect of health education using video media about the benefits of consuming blood supplement tablets during menstruation among young women at the Jamiyyatul Qurro' Islamic Boarding School. Methods: This research is quantitative research, using the Quasi-Experiment method, One grouppretest-posttest approach with a sample size of 70 people, sampling using purposive sampling. Theresearch instrument used video media with a duration of 3 minutes 25 seconds, a pretest-posttestknowledge measuring tool with a knowledge level questionnaire about the benefits of consumingblood supplement tablets during menstruation. Bivariate analysis used the Wilcoxon test. Results: The level of knowledge about the benefits of consuming blood supplement tablets during menstruation in thepretest was at a fair level of 48 respondents (68.6%) and at a good level in the posttest was 63 respondents (90%). The results of the Wilcoxon test obtained a p value of 0.000 (p < 0.05), meaning that there was an influence of health education using video media about the benefits of consuming blood-enhancing tablets during menstruation among young women at the Jamiyyatul Qurro' Islamic Boarding School. Conclusion: There is an influence of health education using video media about the benefits of consuming blood supplement tablets during menstruation among young women at the Jamiyyatul Qurro' Islamic Boarding School. The results of this research further increase the knowledge of young women about the benefits of consuming blood supplement tablets during menstruation, because high knowledge will increase the consumption of blood supplement tablets during menstruation.